2016
DOI: 10.1159/000443311
|View full text |Cite
|
Sign up to set email alerts
|

The Microphthalmia-Associated Transcription Factor p.E318K Mutation Does Not Play a Major Role in Sporadic Renal Cell Tumors from Caucasian Patients

Abstract: Objective: The transcription factor MITF (microphthalmia-associated transcription factor) is known to induce expression of hypoxia-inducible factor (HIF1-α), which is involved in renal carcinogenesis. The MITF p.E318K mutation leads to deficient SUMOylation of MITF, resulting in enhanced activation of its target genes. A case-control study on melanoma patients who coincidentally were affected by renal cell carcinoma (RCC) has revealed an elevated risk for mutation carriers to be affected by one or both of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
1
17
1
Order By: Relevance
“…Concerning the role of the p.E318K variant in the predisposition to tumors other than melanoma, we confirm the association with renal cell carcinoma (RCC) previously described [6,7,[13][14][15]. The association with pancreatic cancer we previously observed in a smaller series of patients [13] was not confirmed here, and therefore remains to be further explored.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Concerning the role of the p.E318K variant in the predisposition to tumors other than melanoma, we confirm the association with renal cell carcinoma (RCC) previously described [6,7,[13][14][15]. The association with pancreatic cancer we previously observed in a smaller series of patients [13] was not confirmed here, and therefore remains to be further explored.…”
Section: Discussionsupporting
confidence: 83%
“…Due to the above-mentioned links with melanoma and kidney cancer susceptibility, current research is focusing on the relationship between p.E318K and the clinicophenotypic features of individuals carrying this variant [9,[11][12][13][14][15][16]. However, current literature on dermoscopic features of nevi and melanomas in these patients is still limited, and predisposition to non-melanoma cancers according to MITF germline status needs to be further investigated [11,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Bertolotto et al identified over a fivefold increased risk for carriers to develop RCC, melanoma, or both cancers in 829 patients (OR 5.55; 95% CI 2.59-12.91; p = 1.2E−6) and identified a fivefold risk of developing RCC only in 164 "genetically-enriched" patients who were wild-type for RCC-predisposing genes (OR 5.19; 95% CI 1.37-16.87; p = 0.008) 2 . In contrast, other studies did not find an association with sporadic RCC 5,12,13 . Ghiorzo et al identified a 31-fold increased risk of melanoma in carriers with a personal or family history of pancreatic cancer (OR 30.85; 95% CI 6.85-138.9; p = 0.0005), but did not find significant enrichment of the variant in sporadic pancreatic cancer patients (0/210 patients had the variant) 4 11 .…”
Section: Resultsmentioning
confidence: 64%
“…Thus, MITF(E318K) may play a role in driving cancer formation in a subset of "genetically-enriched" RCC patients by a still undisclosed biological mechanism. Of note, several other researchers have also failed to identify an association of sporadic RCC with MITF(E318K) 5,12,13 . This may also explain Ghiorzo et al 's findings, as their association was only noted in melanoma patients with a personal or family of pancreatic cancer, and not in patients with sporadic pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation